2013
DOI: 10.2320/matertrans.m2012251
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Pressure Treatment on Microstructure Evolution of Cu–Zn Alloy

Abstract: The ordereddisordered phase transformation temperature and time of CuZn alloy before and after 2 GPa pressure treatment were measured by differential scanning calorimeter (DSC). The phase transformation activation energy and Avrami exponent were calculated and the effect of 2 GPa pressure treatment on the microstructure evolution was also discussed based on the kinetic parameters. The results show that 2 GPa pressure treatment on CuZn alloy from ordered (¢A) to disordered (¢) phase transformation shift to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Infiltration method is a common choice, but it makes the alloy poor compactness [10],eventually limiting the application of Cu-Cr alloys. In recent years, it is reported that high temperature and high pressure can facilitate the compactness of copper alloys with considerable properties [11][12][13][14]. Wu et al [15] has applied high pressure treatment on Cu-Al alloys and the results showed that the hardness and the elastic recovery rate of Cu-Al alloy increase by 13.14% and 71.84%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Infiltration method is a common choice, but it makes the alloy poor compactness [10],eventually limiting the application of Cu-Cr alloys. In recent years, it is reported that high temperature and high pressure can facilitate the compactness of copper alloys with considerable properties [11][12][13][14]. Wu et al [15] has applied high pressure treatment on Cu-Al alloys and the results showed that the hardness and the elastic recovery rate of Cu-Al alloy increase by 13.14% and 71.84%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there are many studies on optimizing microstructure and properties of the metal materials achieved by high pressure treatment [1][2][3], but there are few reports about the effect of high pressure treatment on creep properties of the metal materials. The creep property is one of the main bases for the evaluation of the mechanical properties of the metal materials.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of high pressure processing to improve the study of microstructure and properties of metallic materials are more [1][2][3], but the influence on the creep properties of high pressure treatment on metal materials reported less. The creep property is one of the main basis to evaluate the mechanical properties of the material.…”
Section: Introductionmentioning
confidence: 99%